The role of indenter radius on spherical indentation of high purity magnesium loaded nearly parallel to the c-axis. (August 2017) - Nayyeri, Ghazal; Poole, Warren J.; Sinclair, Chad W.; Zaefferer, Stefan
Abstract: The current work proposes two main contributions based on a study of the effect of indenter radius on spherical indentation of magnesium where loading is nearly parallel to the c-axis. First, it is illustrated that high purity magnesium shown a strong indentation size effect for spherical indentation. The CRSS for basal slip and extension twinning are estimated by extrapolation of the RSS data for an infinitely large indenter radius. Second, it is shown that the number of twins which de-twin during unloading depends on the indenter size, indentation depth, and the magnitude of the plastic strain and stress under the indenter. Graphical abstract: